Functional analysis of the YCF 45 gene in procyclic Trypanosoma brucei - Týč, Jiří (Jihočeská univerzita, 2008)
In this study was shown by RNA interference that YCF 45 gene of putative chloroplast origin is not essential for surviving of procyclic Trypanosoma brucei. Three different construct bearing HA-tagged YCF 45 protein that differs on their N-terminus were generated to reveal the localization of the protein in the cell. Spliced leader acceptor site of YCF 45 mRNA was identified and in comparison to annotated data new start codon was proposed. Fylogeny tree was made to shed some light on the origin of this gene.
Functional analysis of the YCF 45 gene in procyclic Trypanosoma brucei
Keywords: RNA interference; chloroplast; kinetoplastids; HA-tag